Algebraic topology - Spanier Edwin H (New York Springer-Verlag, 1966)
This book is an exposition of the fundamental ideas of algebraic topology. The first third of the book covers the fundamental group, its definition and its application in the study of covering spaces. The focus then turns to homology theory, including co
Keywords: Algebraic topology